Nutrient Recovery from Wastewater Using Desalination Reject Brine - Kamel, Alaa Yasser Ahmed Fouad (2020)
A Master of Science thesis in Civil Engineering by Alaa Yasser Ahmed Fouad Kamel entitled, “Nutrient Recovery from Wastewater Using Desalination Reject Brine”, submitted in November 2020. Thesis advisor is Dr. Kazi Parvez Fattah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).